Food neophobia associates with poorer dietary quality, metabolic risk factors, and increased disease outcome risk in population-based cohorts in a metabolomics study. Issue 1 (4th June 2019) - Sarin, Heikki V; Taba, Nele; Fischer, Krista; Esko, Tonu; Kanerva, Noora; Moilanen, Leena; Saltevo, Juha; Joensuu, Anni; Borodulin, Katja; Männistö, Satu; Kristiansson, Kati; Perola, Markus
ABSTRACT: Background: Food neophobia is considered a behavioral trait closely linked to adverse eating patterns and reduced dietary quality, which have been associated with increased risk of obesity and noncommunicable diseases. Objectives: In a cross-sectional and prospective study, we examined how food neophobia is associated with dietary quality, health-related biomarkers, and disease outcome incidence in Finnish and Estonian adult populations. Methods: The study was conducted based on subsamples of the Finnish DIetary, Lifestyle, and Genetic determinants of Obesity and Metabolic syndrome (DILGOM) cohort ( n = 2982; age range: 25–74 y) and the Estonian Biobank cohort ( n = 1109; age range: 18–83 y). The level of food neophobia was assessed using the Food Neophobia Scale, dietary quality was evaluated using the Baltic Sea Diet Score (BSDS), and biomarker profiles were determined using an NMR metabolomics platform. Disease outcome information was gathered from national health registries. Follow-up data on the NMR-based metabolomic profiles and disease outcomes were available in both populations. Results: Food neophobia associated significantly (adjusted P < 0.05) with health-related biomarkers [e.g., ω-3 (n–3) fatty acids, citrate, α1 -acid glycoprotein, HDL, and MUFA] in the Finnish DILGOM cohort. The significant negative association between the severity of food neophobia and ω-3 fatty acids was replicated in all cross-sectional analyses in the Finnish DILGOM and Estonian Biobank cohorts. Furthermore, food neophobia was associated with reduced dietary quality (BSDS: β: −0.03 ± 0.006; P = 8.04 × 10 −5 ), increased fasting serum insulin (β: 0.004 ± 0.0013; P = 5.83 × 10 −3 ), and increased risk of type 2 diabetes during the ∼8-y follow-up (HR: 1.018 ± 0.007; P = 0.01) in the DILGOM cohort. Conclusions: In the Finnish and Estonian adult populations, food neophobia was associated with adverse alteration of health-related biomarkers and risk factors that have been associated with an increased risk of noncommunicable diseases. We also found that food neophobia associations with ω-3 fatty acids and associated metabolites are mediated through dietary quality independent of body weight.